Una aplicación de las series de lie en el estudio del problema de los dos cuerpos clásico (2009)
The classical two-body problem is analyzed by Lie series through a common regularization. It is showed that by an appropriate change of the independent variable (introducing a pseudo-time) is possible to obtain six differential equations which, integrated by Lie series, give short expressions for the components of the position and velocity vectors. In principle, the expressions are valid for the conics and the rectilinear motion.